BODY COMPOSITION AND RESPIRATORY PARAMETER ANALYSIS AT FOOTBALL PLAYERS - Spirkoska Vangelovska, Biljana; Dejanova, Beti; Karagjozova, Ivanka; Mihaela Nestorova; Vangel Ristovski (ANTHROPOLOGICAL SOCIETY OF SERBIA, 2023)
Pulmonary function tests (PFTs) are commonly used for evaluating respiratory status and managing persons with known pulmonary disease. They have become part of routine health examinations in respiratory, occupational, and sports medicine, and in public-health screening. The results of PFTs are interpreted in relation to normal range reference values, as recommended by the guidelines of the American Thoracic Society (ATS) and the European Community forCoal and Steel (ECCS). Spirometry is a gold standard pulmonary function test that measureshow an individual inhales or exhales volumes of air as a function of time. It is the mostimportant and most frequently performed pulmonary function testing procedure, having becomeindispensable for the prevention, diagnosis, and evaluation of various respiratory impairments. Anumber of 61 football players were divided into 2 groups according to their age, 13 (13.85 ± 3.26) and27 years (23.82 ± 3.32). This study was organized by the Institute of Medical, Experimentaland Applied Physiology and Anthropology, Medical faculty – UKIM, Skopje. The spirometry method was performed with the Spirobank II spirometer (Rome, Italy), for the followingparameters: forced vital capacity (FVC), forced expiratory volume in the first second (FEV1),and the ratio FEV1/FVC ratio.Body composition analyzer InBody 720, Great Britain, was usedto determine body weight (kg), body height (cm), body mass index - BMI weight (kg / m 2 ),skeletal muscle mass SMM (kg) and the amount of proteins (kg) and minerals (kg). We did notfind any statistically significant differences for forced vital capacity (FVC), forced expiratoryvolume in the first second (FEV1), and the ratio FEV1/FVC ratio.
Keywords: spirometry; pulmonary function; body composition